Deposition of Ti-Si-N films on Al substrates by magnetron sputtering. (1st November 2013) - Pang, J; Bai, Y; Qin, F; Pan, L; Zhao, Y; Kang, R
<x xml:space="preserve">Abstract</x> The objective of this work is to settle the problem of adhesion between hard films and soft metal substrates. Hard Ti-Si-N films were deposited onto soft Al substrates with a double target magnetron sputtering system. The composition, structure, surface morphologies and mechanical properties were characterised by electron probe microanalyser, X-ray diffraction, atomic force microscope, scratch test and nanoindentation respectively. The as-deposited films had good adhesion to the Al substrates and had a smooth and lustrous surface. The maximum hardness of the films achieved was as high as 27·2 GPa at the Si target power of 80 W.